Peran Budaya Organisasi Dalam Meningkatkan Kinerja Karyawan PT Putratama Satya Bhakti: The Role of Organizational Culture in Improving Employee Performance at PT Putratama Satya Bhakti - Tania Narindra Dewita; Achmad Fauzi; Dian Sudiantini (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research uses qualitative methods by collecting observational data in the field, interviews with informants, and documentation. The informant selection technique in this research was a purposive sampling technique. The analysis method uses data triangulation from Miles and Huberman (2014). Data analysis used by researchers is using the help of NVivo 12 Pro software. The results of this research show that the company's core values, including honesty, effectiveness, responsibility, and quality, are implemented through programs to support employee performance improvement, namely human capital development programs, emotional and spiritual intelligence control programs, corporate social responsibility (CSR) programs, and employee welfare. The obstacles experienced in implementing organizational culture are poor communication patterns, generation gaps, and inconsistency in implementing culture due to indiscipline on the part of some employees. Keywords: Organizational Culture; Employee Performance